2015
DOI: 10.1016/j.bbadis.2015.08.012
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 inhibition induces mitochondrial fusion, autophagic flux and reduces diffuse mutant huntingtin in striatal neurons

Abstract: Striatal neurons are vulnerable to Huntington's disease (HD). Decreased levels of acetylated alpha-tubulin and impaired mitochondrial dynamics, such as reduced motility and excessive fission, are associated with HD; however, it remains unclear whether and how these factors might contribute to the preferential degeneration of striatal neurons. Inhibition of the alpha-tubulin deacetylase HDAC6 has been proposed as a therapeutic strategy for HD, but remains controversial - studies in neurons show improved intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 70 publications
5
46
0
Order By: Relevance
“…Mitochondrial fragmentation has been reported in peripheral cells of HD patients [49,160]. Consistently, significant changed expression or post-translational modifications of mitochondrial fusion and fission regulators such as Drp1, Mitofusions, and Fis1 was also observed in the brains of patients with HD [160,161,162]. For example, increased Drp1 S-nitrosylation were observed in the striatum of a transgenic mouse model of HD and HD patients, which correlated with excessive mitochondrial fragmentation followed by loss of dendritic spines, signifying synaptic damage [163].…”
Section: Mitochondrial Dynamics Mitochondrial Function and Neuronmentioning
confidence: 57%
“…Mitochondrial fragmentation has been reported in peripheral cells of HD patients [49,160]. Consistently, significant changed expression or post-translational modifications of mitochondrial fusion and fission regulators such as Drp1, Mitofusions, and Fis1 was also observed in the brains of patients with HD [160,161,162]. For example, increased Drp1 S-nitrosylation were observed in the striatum of a transgenic mouse model of HD and HD patients, which correlated with excessive mitochondrial fragmentation followed by loss of dendritic spines, signifying synaptic damage [163].…”
Section: Mitochondrial Dynamics Mitochondrial Function and Neuronmentioning
confidence: 57%
“…However, at a later time point DRG mitochondrial function also normalized, indicating that HDAC6 may not only affect mitochondrial transport but also mitochondrial health (Figure 6). Thus it is of interest that HDAC6 inhibition has been shown to induce mitochondrial fusion/elongation and movement in neuronal cultures [20], and it has been proposed that elongated mitochondrial networks are more efficient at energy production [33; 45]. Although the exact mechanism of how HDAC6 inhibition enhances mitochondrial bioenergetics in our model is still to be determined, our data clearly shows that pharmacological inhibition of HDAC6 with ACY-1083 slowly reverses mitochondrial bioenergetic deficits in the peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of HD, it is striatal medium spiny neurons that are preferentially lost. Although the basis for this selective vulnerability is unknown, certain studies have found that striatal neurons are prone to mitochondrial fragmentation, due to increased expression of the Drp1 receptor Fis1 (43), a pro-fission effect of dopaminergic signaling (40), or increased S-nitrosylation of Drp-1 (41). Thus, in HD, the energy demands of medium spiny neurons, together with a predisposition to fragmentation of the mitochondrial network, may explain why PPARδ transcription interference contributes to HD pathogenesis, and why PPARδ promotion of mitochondrial fusion in HD is neuroprotective.…”
Section: Discussionmentioning
confidence: 99%